Correlation of Birth Weight/Length Ratio to Skinfold Thickness in Full-Term Newborns - Asril Aminullan; Yuliatmoko Suryatin; Taralan Tambunan (Paediatrica Indonesiana, 1999)
The determination of child/neonatal nutritional status based on their skinfold thickness has been widely known and accepted, but its daily implementation is quite difficult since this procedure needs specific tools and skills. Although still debatable, some anthropometric measurements, i.e., birth weight/length ratio were currently used as a mean to determine one's nutritional status. To find out the correlation of birth weight/length ratio to skinfold thickness of newborn babies based on gender, a cross-sectional study was conducted on 352 full-term infants (194 males, 158 females) born at the Cipto Mangunkusumo Hospital between June 14 to July 17, 1998. Of the male infants, their birth weight/length ratio showed a strong correlation to triceps and subscapular thickness (r=0.65 and 0.68, respectively); while the females revealed a strong correlation of birth weight/ length ratio to the triceps thickness (r=0.51) and a moderate correlation to the subscapular skin fold thickness (r=0,49). It was also found that the triceps and subscapular skinfold thickness in male infants were significantly lesser thanÂ  the females, with p values of 0.02 and 0.04, respectively. This study revealed that the birth weight/length ratio can be used as a mean to assess neonatal nutritional status.